Opini Mahasiswa Terhadap Pelaksanaan Kuliah Kerja Nyata (KKN) di Universitas Merdeka Madiun - Azola Dwi Yuliasari; Nunik Hariyani; veny Ari Sejati (Universitas Merdeka Madiun, 2022)
Abstract– The aims of this study were (1) to find out student opinions in the implementation of Real Work Lectures at the Merdeka University of Madiun; (2) to find out the process of forming student opinions in the implementation of Real Work Lectures at the Merdeka University of Madiun; and (3) to determine the factors that influence the formation of student opinions in the implementation of Real Work Lectures at the Merdeka University of Madiun. This study is a qualitative descriptive study where the data obtained from the study were analyzed in words without using statistical methods which were then drawn conclusions. The purpose of descriptive research in this study is to describe student opinions in the implementation of the Merdeka Madiun University Real Work Lecture. The population or subjects of this study were students participating in the Real Work Lecture, the Chair of the LPPM, the Chair of the KKN Committee, the KKN Monev Team, Field Supervisors and Village Heads. Data collection techniques in this study using interviews and observation. While the analytical method used in this research is to use qualitative analysis methods, namely methods that aim to provide a comprehensive picture of the subject under study and are not intended to test hypotheses. The conclusion of the study shows that (1) students' opinions on the implementation of Real Work Lectures are mostly supportive and some are not; (2) student opinion is formed by perception. Furthermore, opinions can lead to attitudes in the form of feelings, understanding and behavior. After the opinion that gives rise to an attitude will lead to an agreement which will later lead to public opinion;and (3) the factors forming students' opinions on the implementation of the Real Work Lecture include cultural factors, past experiences, values held by the community and branching news. Keywords : Opinion, Students, Real Work Lectures.